OP0160 Response and drug survival of 1st TNF inhibitor in 370 patients with psoriatic arthritis in a real life setting – what is the role of co-medication with methotrexate?. (23rd January 2014) - Fagerli, K.M.; Lie, E.; van der Heijde, D.; Heiberg, M.S.; Kalstad, S.; Rødevand, E.; Mikkelsen, K.; Lexberg, Å. S.; Kvien, T.K.
Abstract : Background: It is well established that methotrexate (MTX) co-medication improves efficacy of TNF-inhibitors (TNF-i) in rheumatoid arthritis, while in ankylosing spondylitis it is widely accepted that it does not. The role of MTX co-medication in psoriatic arthritis (PsA) is still unclear. Objectives: Investigate if patients receiving concomitant MTX have better responses and drug survival to their 1st TNFi. Methods: Data are from the NOR-DMARD register, an observational study of adult patients with inflammatory arthropathies starting DMARD-treatment, initiated in 2000. Patients with PsA receiving their 1st TNFi, either combined with MTX or with no concomitant DMARD, were selected. Due to heterogeneous symptomatology of patients, selected outcome measures were patient and physician global assessments, MHAQ and SF-6D. Baseline characteristics and state and change at 3 months were compared by two-sample t-test and χ 2 test, as appropriate. 3-year drug survival was compared using Kaplan-Meier analysis with log-rank test. Results: 370 patients were included in these analyses. We found significant baseline group differences regarding the percentage of patients with ≥1 swollen joint and SF6D scores (table 1 ). Eleven patients in the MTX combo group and 14 patients in the mono group stopped mediation before 3 months follow-up, and an additional 60 patients had not yet attended or missed their 3-month visit. Three-month states and responses were similar between the groups, with statistically significant differences only for physician global. We did however find improved 3-year drug survival in the combination group (p=0.04). Conclusions: Our data did not show significant impact of MTX co-medication on responses in PsA patients completing 3 months of treatment with their first TNFi. However, drug-survival was better in patients receiving concomitant MTX. Disclosure of Interest: K. Fagerli Speakers Bureau: Abbott, Roche, MSD, Pfizer, E. Lie: None Declared, D. van der Heijde: None Declared, M. Heiberg: None Declared, S. Kalstad: None Declared, E. Rødevand: None Declared, K. Mikkelsen: None Declared, Å. Lexberg: None Declared, T. Kvien: None Declared